Exploring quality programs for English language learners in charter schools: A framework to guide future research - Garcia, Peggie; Morales, P. Zitlali (Education Policy Analysis Archives, 2016)
Although there has been a great deal of debate about the effectiveness of charter schools in the research literature, there has been surprisingly little attention paid to English language learners (ELLs) in charter schools. Moreover, the charter school research has predominantly focused on whether or not charter schools are effective rather than how or why high-performing charter schools work, particularly for ELLs. We contend that researchers must expand their focus beyond access and achievement and begin to grapple with questions related to the quality of programs for ELLs in charter schools. To meet an emerging need in the field, we synthesize several strands of existing research—related to charter schools, school improvement, and ELLs in traditional public schools—to propose a five-component framework that describes essential elements of quality programs for ELLs in charter schools. We conclude with a discussion of implications of our framework for research, policy, and practice.